Could the link between drug addiction in adulthood and substance use in adolescence result from a blurring of the boundaries between incentive and hedonic processes? - Kehinde F; Oduyeye O; Mohammed R (Dove Medical Press, 2019)
Fiona Kehinde,1 Opeoluwa Oduyeye,2 Raihan Mohammed11Faculty of Medicine, University of Cambridge, Cambridge, UK; 2Faculty of Medicine, Imperial College School of Medicine, London, UKAbstract: There is a broad consensus that the development of drug addiction in adulthood is closely linked to the onset of drug use in adolescence. However, the relationship between drug exposure during adolescence and subsequent vulnerability to addiction is yet to be fully understood. This review will first use evidence from adult studies on reward and addiction to give an up-to-date reference point of normal reward-circuitry and the maladaptive changes that later occur in addiction. This will then be compared with current evidence from adolescent studies on reward-circuitry. Similarities between the reward processes governing characteristic behavioral traits in adolescence and the reward profile in adult addiction could help to explain why the risk of later developing addiction is increased when substance use is initiated in adolescence. We argue that the age of onset is a major risk factor in the development of substance use disorder due to a blurring of the boundaries between incentive and hedonic processes, which occurs during adolescence. A deeper understanding of the processes that mediate this blurring could open new avenues for the prevention and treatment of adult drug addiction.Keywords: addiction, dopamine, impulsive, compulsive, opiate